A Commentary on Innovation and Emerging Scientific Careers: Is Social Work Prepared to Compete in Today's Scientific Marketplace?. (March 2017) - Craddock, Jaih B.
The aim of this article is to address some of the questions Dr. Paula S. Nurius presents in her article, Innovation and Emerging Scientific Careers: Is Social Work Prepared to Compete in Today‖s Scientific Marketplace? Specifically, this article will focus on what we can do to better prepare our emerging research scholars to be successful innovators through trans-disciplinary training and educational activities. This article recommends two main ideas. The first main idea is that social work co-host meetings, lectures, roundtables and trainings with disciplines we do not tend to collaborate with, in order to build inter-disciplinary partnerships. The second suggestion is that students are socially integrated, via extensive interaction of outside disciplines, through customized semester-long rotation style trainings. By implementing these suggestions, we will be providing a space for our doctoral students to gain an understanding of how different disciplines‖ researchers, technologies, and/or methods can add to their ability to produce innovative ideas, encouraging creative and complex thinking and problem solving.